Caffeinated chewing gum improves sympathetic nerve activity and wrestling performance: a double-blind crossover trial - Tzeng, G.-J.; Lin, H.-Y.; Shiu, Y.-J.; Hsieh, M.-H.; Chen, Z.-C.; Chiu, C.-H. (International Journal of Sports Physiology and Performance, 2026)
Purpose: This study investigated the effect of caffeinated chewing gum on sympathetic nerve activity and simulated wrestling performance.